2022
DOI: 10.1038/s41420-022-01225-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel BH3 mimetic Bcl-2 inhibitor promotes autophagic cell death and reduces in vivo Glioblastoma tumor growth

Abstract: Anti-apoptotic members of the Bcl-2 family proteins play central roles in the regulation of cell death in glioblastoma (GBM), the most malignant type of brain tumor. Despite the advances in GBM treatment, there is still an urgent need for new therapeutic approaches. Here, we report a novel 4-thiazolidinone derivative BH3 mimetic, BAU-243 that binds to Bcl-2 with a high affinity. BAU-243 effectively reduced overall GBM cell proliferation including a subpopulation of cancer-initiating cells in contrast to the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Compounds such as BH3-mimetics which target the BCL-2 proteins that negatively regulate BECLIN1, could also be a therapeutic option, although they may potentially activate apoptotic pathways [ 130 ]. Interestingly, a recent report suggested that BH3-mimetics can be developed that selectively target the BCL-2:BECLIN1 interaction over interactions with pro-apoptotic proteins [ 131 ], whilst another study showed cell-type selective induction of autophagy (albeit autophagic death) versus apoptosis in response to BH3-mimetics [ 132 ]. However, neither BH3-mimetics nor Tat-Beclin is yet to be investigated in IBD models.…”
Section: Targeting Autophagy To Treat Ibdmentioning
confidence: 99%
“…Compounds such as BH3-mimetics which target the BCL-2 proteins that negatively regulate BECLIN1, could also be a therapeutic option, although they may potentially activate apoptotic pathways [ 130 ]. Interestingly, a recent report suggested that BH3-mimetics can be developed that selectively target the BCL-2:BECLIN1 interaction over interactions with pro-apoptotic proteins [ 131 ], whilst another study showed cell-type selective induction of autophagy (albeit autophagic death) versus apoptosis in response to BH3-mimetics [ 132 ]. However, neither BH3-mimetics nor Tat-Beclin is yet to be investigated in IBD models.…”
Section: Targeting Autophagy To Treat Ibdmentioning
confidence: 99%
“…by directly displacing the BH3 domain-containing protein Beclin-1 from BCL2 or BCL-X L [ 22 , 27 ]. In this regard, the induction of mitophagy may either represent a survival mechanism or lead to cell death [ 28 , 29 ]. Several observations in our study support the induction of mitophagy selectively during CICD but not during apoptotic cell death, including the ultrastructural analysis, the accumulation of LC3-II associated with increased autophagosome formation, and lastly the loss of mitochondrial mass suggested by staining with MitospyGreen and loss of cytochrome c and TOMM20.…”
Section: Discussionmentioning
confidence: 99%
“…Computational modeling has enabled the development and characterization of novel powerful small-molecular inhibitors. Examples include homology modeling to determine the structure of protein complexes and screening of libraries such as the Specs SC small molecule library for the identification of appropriate candidates for therapeutic purposes in GBM [ 134 , 135 , 136 ]. The creation of such libraries, the development of computational modeling, and the combination of these novel techniques with those described in this review article reveal a hopeful future for the targeted therapeutics in GBM.…”
Section: Discussionmentioning
confidence: 99%